Analisis Keterlambatan Pelaksanaan Pekerjaan Jalur Kereta Api Lintas Makassar – Parepare - Adetomo, Agung (Program Studi Teknik Sipil Universitas Bosowa, 2023)
The train is a means of mass transportation which generally consists of a locomotive and a series of trains or carriages. The series of trains or carriages are relatively large in size so that they are able to load passengers and goods on a large scale. For the transportation of goods in large quantities, a series of more than 50 trains drawn and/or pushed with several locomotives can be used, such as the Babaranjang train in South Sumatra.The train is an efficient transportation for a high number of passengers so it is very suitable for mass transportation of urban trains in congested corridors, but is also used for medium-distance passenger transportation or for the transportation of goods in large quantities. Because of its nature as an effective mass transportation, several countries are trying to make maximum use of it as the main means of land transportation both within cities, between cities, and between countries